2009
DOI: 10.1002/art.24881
|View full text |Cite
|
Sign up to set email alerts
|

The infrapatellar fat pad in knee osteoarthritis: An important source of interleukin‐6 and its soluble receptor

Abstract: Objective. Obesity is a potent risk factor in knee osteoarthritis (OA). It has been suggested that adipokines, secreted by adipose tissue (AT) and largely found in the synovial fluid of OA patients, derive in part from the infrapatellar fat pad (IFP), also known as Hoffa's fat pad. The goal of this study was to characterize IFP tissue in obese OA patients and to compare its features with thigh subcutaneous AT to determine whether the IFP contributes to local inflammation in knee OA via production of specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(182 citation statements)
references
References 13 publications
9
167
1
5
Order By: Relevance
“…When the subcutaneous fat tissue (SCFT) and fat pad tissue (FPT)-derived cells were compared, IPFP adipocytes showed a twofold increase in IL-6 gene expression and in IL-6 release. Interestingly, leptin secretion was 40 % lower and adiponectin was increased by 70 % in IPFP cells compared with the subcutaneous adipose tissue [73]. Moreover, it was demonstrated that the culture media from OA patients' IPFP adipocytes induced MMP13 and MMP1 expression in articular chondrocytes and that the leptin level positively correlated with the expression of both MMPs and cartilage collagen destruction [20].…”
Section: Adipocytokines Secretion By Infrapatellar Fat Padmentioning
confidence: 98%
“…When the subcutaneous fat tissue (SCFT) and fat pad tissue (FPT)-derived cells were compared, IPFP adipocytes showed a twofold increase in IL-6 gene expression and in IL-6 release. Interestingly, leptin secretion was 40 % lower and adiponectin was increased by 70 % in IPFP cells compared with the subcutaneous adipose tissue [73]. Moreover, it was demonstrated that the culture media from OA patients' IPFP adipocytes induced MMP13 and MMP1 expression in articular chondrocytes and that the leptin level positively correlated with the expression of both MMPs and cartilage collagen destruction [20].…”
Section: Adipocytokines Secretion By Infrapatellar Fat Padmentioning
confidence: 98%
“…Likewise, in cultured chondrocytes, as already mentioned for RA, adiponectin also induces the production of proinflammatory and matrix catabolic factors (96). In keeping with all of these activities for adiponectin in OA, it has been determined that the infrapatellar fat pad of knee OA has an increased synthesis of adiponectin that suggests the infrapatellar fat pad as a possible source of joint adiponectin (105).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 61%
“…The knee joint is the only joint in which there is localized adipose tissue, recognized also as being metabolically active [20][21][22][23]25], and the joint most often affected by OA. While previous…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the knee likely provides an ideal setting in which to examine any potential role(s) of fat on OA development/progression, particularly as it is the only joint to contain a large intra-articular deposit of adipose tissue. The infrapatellar fat pad (IFP) is an intracapsular and extrasynovial structure, distinguishable from SAT and VAT by its unique location and relative size [19][20][21][22][23][24]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation